2008 Bicycle Master Plan update, city of Manhattan, Kansas - Bunger, Chad (Kansas State University, 2008)
In 1998, the City of Manhattan, Kansas and Kansas State University jointly developed a City of Manhattan Bicycle Master Plan. This plan created a vision for bicycling in the community, established goals and designated streets to be improved with bicycle facilities. The Master Plan also developed recommendations to incorporate bicycle facility planning into the growth of Manhattan. This plan created a solid political foundation that showed that bicycling matters in Manhattan, Kansas. However, the 1998 Bicycle Master Plan lacked specifics on how to incorporate these recommendations and routes into the existing and future street system. The 2008 Bicycle Master Plan Update attempts to address the shortcomings of the 1998 Master Plan and incorporate the growth and expansion of the City since 1998. The initial step of the Bicycle Master Plan Update was to calculate a Bicycle Safety Index. The Bicycle Safety Index was modeled after previous research conducted on the City of Manhattan, where street and land use attributes, such as road surface materials, street width, traffic volume, presence of angled-parking and traffic speeds were weighted and calculated in a spatial environment using GIS software. The result was a rating of all streets in Manhattan based on their suitability for safe bicycle travels. Using the results of the Bicycle Safety Index, specific routes were developed based on their proximity to bicycle destinations, such as commercial areas, schools and parks. Routes were created by using ESRI's Network Analyst software. Routes proposed by the software were evaluated by a windshield and handlebar survey to ultimately determine the appropriateness of each route. Following the determination of the proposed routes, specific facility recommendations for each street segment were proposed based on the traffic volume, vehicle speeds, street widths and the geometry of the segment. General recommendations and funding options were created to assist in the advancement of the goals and objectives originally initiated in the 1998 Master Plan. The result is a Master Plan that can be used by City Planners to incorporate bicycle transportation into the City and a map for bicyclist to travel from one place to another in the City safely.
Keywords: Bicycle; Bicycle routes; Bicycle master plan; Urban and Regional Planning (0999)